Função a partir de uma perspectiva histórica - Franco, Paula Andressa Adamski; da Silva, Karolina Barone Ribeiro [UNESP] (My University, 2017)
This paper reports a finalized study, which had the theme function, being used literature to determine how the concept of function has been treated in historical form with respect to learning the concept by undergraduate students in mathematics and basic education. According to the research carried out, it was possible to note that the concept of function through a historical approach, it is still a methodology being little used in the classroom, as a pedagogical tool, but it has been increasing gradually.
Function from a historical perspective
Keywords: Basic education in mathematics; Function; History of mathematics